Extraction, analysis, and antifungal activity study of algae antibiotic active substances in plateau lakes - Jing Zhao; Ju Tang; Zhandi Wang; Shahzad Munir; Rong Jiao; Jia Li; Kaixiang Chao; Qionglian Wan; Lianchun Wang; Changbing Ye (PLoS ONE, 2025)
This study was carried out to assess the inhibitory activity of algae in plateau lakes against plant pathogenic fungi, and further conduct preliminary research and analysis on their antifungal active ingredients, in order to provide a certain basis for the development and utilization of algal secondary metabolite as anti-plant pathogenic fungal agents. Different solvent extraction methods using water, ethyl acetate, ethanol, and methanol were conducted to extract polyphenol metabolites from Ulothrix, Chlorella vulgaris, and Microcystis pseudofilamentosa Crow. The composition of the extracts was analyzed based on the UPLC-MS/MS detection platform, and the antifungal activity was determined. The results showed that the content of polyphenol metabolites extracted from Ulothrix using methanol was the highest, followed by ethyl acetate and ethanol. The water extraction method resulted in the highest loss of polyphenolic metabolites. Three species of Fusarium oxysporum were used as indicator fungus to determine the antifungal activities of algae extracts. The three types of algae extracts showed good antimicrobial effects on F. oxysporum. The polyphenol metabolites extracted from Ulothrix using methanol demonstrated the strongest antifungal activity, with up to 20 mm in diameter of inhibition zone. The metabolite with the weakest antifungal activity was M. pseudofilamentosa Crow, with an 8-mm diameter of inhibition zone. Based on the UPLC-MS/MS detection, 242 polyphenol metabolites were initially identified in the methanol extracts of the three algae, including 160 phenolic acids, 32 flavonoids, 17 flavonols, 7 dihydroflavones, 2 dihydroflavonols, 2 chalcones, 2 flavanols, 5 flavonoids, 5 lignans, and 10 coumarins. Principal component analysis, fold change analysis, and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis were used to conduct differential metabolite screening and related metabolic pathway enrichment. The methanol extract samples of the three algae were mainly classified into two categories. Ten important differential metabolites and 15 important metabolic pathways were obtained. In addition, the methanol extracts of Ulothrix contained the largest variety of phenolic acid compounds, with a total of 75 phenolic acid compounds detected, which was followed by C. vulgaris, with 44 phenolic acid compounds detected, and M. pseudofilamentosa Crow, with 37 phenolic acid compounds. Compared with phenolic acid compounds, the quantitative differences of other polyphenols were smaller. Based on these results and those from the antifungal experimental analysis, phenolic acids in algae polyphenol metabolites are the main antifungal active ingredients.